Two new species of Syndesmis (Platyhelminthes, Rhabdocoela, Umagillidae) from the sea urchin Pseudechinus magellanicus (Echinodermata, Echinoidea) in the Southwestern Atlantic Ocean - Brusa, Francisco (2017)
In this paper, we describe two new species of Syndesmis living in Pseudechinus magellanicus in the Southwest Atlantic Ocean. The new species have a long stylet in the male reproductive system, which is different from that of the known species of the genus. Specimens of Syndesmis selknami n. sp. have a ~220-mm-long stylet (~1/3 of the body length, 0.69 mm). This ratio is unique because only four species (Syndesmis echinorum, Syndesmis rubida, Syndesmis inconspicua and Syndesmis echiniacuti) have similar stylet lengths but are larger in body sizes (3e5 mm). Specimens of Syndesmis aonikenki n. sp. have a ~148-mm-long stylet (~1/10 of the body length, 1.11 mm). Syndesmis pallida has a similar ratio but the uterus is located posteriorly, and the filament glands are very small and located in the posterior region of the body. These are the first flatworms reported parasitizing Pseudechinus magellanicus.